Residual Stress Control in Drawn Bar and Wire by Heating-Cooling-Drawing Process - Akimoto, Yutaka; Kubota, Hiroaki; Yoshida, Kazunari; Saito, Keigo; Sakurazawa, Wataru (ISIJ International, 2021)
We investigated the drawing process with a temperature gradient in the radial direction of the bar to achieve flexible control of the residual stress in the drawn bar with only the drawing process. The obtained results are as follows: (1) A heating-cooling-drawing process was developed to generate a temperature gradient in the radial direction of the bar. The optimum cooling time was determined by heat conduction analysis. A cooling time of 0.54 s is optimal for a steel bar with a diameter of 10 mm. (2) We experimentally confirmed that the proposed method is extremely effective for controlling the residual stress in a bar or wire. (3) The residual stress decreased by increasing the heating temperature up to 400°C. Above 400°C, the control of stress was small. (4) The combination of the proposed method and extremely small reduction drawing is effective for obtaining strong compressive residual stress in the surface layer. For a 0.4% or 0.6% reduction rate of the section area, residual stress reduction of 900 MPa was obtained. (5) It was confirmed that residual stress is reduced when the material is cooled down after drawing by finite element analysis considering thermal strain. The mechanism of residual stress reduction by the proposed method is the loss of thermal stress due to the drawing process and the thermal contraction at the center during cooling.